Prediction of Width of Un-Erupted Incisors, Canines and Premolars in a Ugandan Population:A Cross Sectional Study - Buwembo, William; Kutesa, Annet; Muwazi, Louis; Rwenyonyi, Charles Mugisha (BMC oral health, 2012)
Accurate prediction of the space forms an important part of an orthodontic assessment in the mixed dentition. However the most commonly used methods of space analysis are based on data developed on Caucasian populations. In order to provide more accurate local data we set out to develop a formula for predicting the widths of un-erupted canines and premolars for a Ugandan population and to compare the predicted widths of the teeth from this formula with those obtained from Moyers’ tables, and Tanaka and Johnston’s equations.Dental casts were prepared using mandibular and maxillary arch impressions of 220 children (85 boys/135 girls) aged 12–17 years recruited from schools in Kampala, Uganda. The mesio-distal width of the mandibular incisors, mandibular and maxillary canines and premolars were measured with a pair of digital calipers. Based on regression analysis, predictive equations were derived and the findings were compared with those presented in Moyers’ probability tables, and Tanaka and Johnston’s equations. There were no statistically significant differences between the tooth widths predicted by our equations and those from Moyers’ probability tables at the 65th and 75th percentile probabilities for the girls and at 75th level in boys in the mandibular arch. While in the maxillary arch no statistically significant differences at the 75th and 95th levels were noted in girls. There were statistically significant differences between predicted tooth sizes using equations from the present study and those predicted from the Tanaka and Johnston regression equations.In this Ugandan population, Moyers’ probability tables could be used to predict tooth widths at specific percentile probabilities, but generally, Tanaka and Johnston technique tends to overestimate the tooth widths.
Keywords: Canines, Incisors, Mesio-distal widths, Prediction equation, Premolars, Ugandan